Combined Color-Doppler Flow and Angio Planewave UltraSensitive™ Imaging for Analysis of Hemodynamic Characteristics of Normal Upper Limb Arteries - Yanzhou Liu; Xiyue Zhang; Hang Yang; Xueyan Tan; Duo Huang; Hongmei Yuan; Lili Yu; Fang Yang; Yuan Zou; Xiuli He; Yuqun Luo; Fangzhao Cui; et al. (Artery Research)
Abstract Background To evaluate the hemodynamic characteristics of normal upper extremity arteries from the brachial artery to the fingertip arterioles. Methods We analyzed the characteristics and changes in the regularities of ultrasonic parameters in the upper extremity arteries of 104 healthy volunteers using color Doppler flow imaging and Angio Planewave UltraSensitive™ imaging. The measured ultrasonic parameters included the vessel diameter, blood-flow spectrum waveform, peak systolic velocity, end-diastolic velocity, resistance index, pulsatility index, ratio of PSV to EDV, blood-flow volume, along with systolic acceleration of each BA, radial artery, superficial palmar arch artery, palmar proper digital artery, and third-grade artery arch of the fingernail bed. Results From BA to FN3AA, the diameter, PSV, RI, S/D, VFlow, and slope of the artery significantly decreased (P < 0.001), and size of the parameters significantly correlated with the anatomic position of the arteries. The blood-flow spectrum gradually changed from various waveforms to fixed monophasic waves. There was a linear relationship between the distribution of monophasic waveforms and arterial groups (R = -0.453; P < 0.001). When the blood-flow spectrum of BA and RA showed a monophasic waveform, their branch arteries showed the same. The waveforms of PPDA and FN3AA were also monophasic. Conclusion Regular changes in the blood-flow spectrum waveform and hemodynamic parameters are related to the anatomic position of the upper limb arteries. CDFI combined with Angio PLUS accurately and systematically evaluates the hemodynamic characteristics of the upper extremity arteries.